THE ROLE OF SOCIAL CAPITAL IN IMPROVING HOUSEHOLD WELFARE (CASE STUDY IN LAMBU DISTRICT, BIMA REGENCY) - Hardinandar, Fajrin; Pratama, Adhi Nurrahman (Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to analyze how the role of social capital in improving household welfare. This study was conducted on households in the Lambu sub-district with an analytical method using probit and Tobit models, as well as a two-way causality relationship between the welfare model and social capital using the TSLS approach. The results of the study show that only bridging capital has an impact on increasing household welfare, due to the complexity of the heterogeneous interactions within it. While bonding capital is only on homogeneous community interactions so that it is less effective in increasing welfare, as well as capital linking which tends to produce distribution bias. The heads of households with more unmarried status are below the poverty line and tend to be active in bridging capital. They are aware that they must be involved in heterogeneous communities to improve their welfare, while married/divorced households tend to be above the poverty line and spend more time in the workplace than active in community activities. Keywords: Bonding capital, bridging, linking, household status, depth of poverty